Krueger/Schiff/Valdes Revisited : Agricultural Price and Trade Policy Reform in Developing Countries since 1960 - Anderson, Kym (World Bank, Washington, DC, 2014)
A study of distortions to agricultural incentives in 18 developing countries during 1960-84, by Krueger, Schiff and Valdes (1988; 1991), found that policies in most of those developing countries were directly or indirectly harming their farmers. Since the mid-1980s there has been a substantial amount of policy reform and opening up of many developing countries, and indicators of that progress have been made available recently by a new study that has compiled estimates for a much larger sample of developing countries and for as many years as possible since 1955. The new study also covers Europe s transition economies and comparable estimates for high-income countries, thereby covering more than 90 percent of world agricultural output and employment. This paper summarizes the methodology used in the new study (pointing out similarities and differences with those used by the OECD and by Krueger, Schiff and Valdes), compares a synopsis of the indicators from Krueger, Schiff and Valdes and the new study for the period to 1984, summarizes the changing extent of price distortions across countries and commodities globally since then, and concludes by evaluating the degree of distortion reduction over the years since 1984 compared with how much still remains, according to the results of a global economy wide model.